1996
DOI: 10.1159/000213792
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of an Inactivated Split Influenza Vaccine in Institutionalized Elderly Patients

Abstract: The immunogenicity of influenza vaccination in elderly institutionalized patients, with a variety of clinical disorders, was tested in an open multicenter study involving 495 people (mean age 80 years). Vaccination with an inactivated split influenza vaccine (FluarixTM) was clinically well tolerated. For all age ranges and all strains of virus, the vaccine elicited a humoral response which surpassed the European Community requirements for influenza vaccines in adults over 60 years. The geometric mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 0 publications
2
25
0
Order By: Relevance
“…In accordance with recent data of Van Hoeke et al [11], the HI antibody postvaccination response of institutionalized subjects quantitatively exceeded the requirements of the European Commission for Influenza Vaccines for adults over 60 years [12], i.e., MFI of GMT 12, seroprotection 160%, and seroconversion rate 130% (table 2). Indeed, the MFI values ranged from 3.4 to 5.5, seroprotection from 70 to 84%, and positive responses from 58 to 69%.…”
Section: Discussionsupporting
confidence: 89%
“…In accordance with recent data of Van Hoeke et al [11], the HI antibody postvaccination response of institutionalized subjects quantitatively exceeded the requirements of the European Commission for Influenza Vaccines for adults over 60 years [12], i.e., MFI of GMT 12, seroprotection 160%, and seroconversion rate 130% (table 2). Indeed, the MFI values ranged from 3.4 to 5.5, seroprotection from 70 to 84%, and positive responses from 58 to 69%.…”
Section: Discussionsupporting
confidence: 89%
“…We identified 60 eligible articles published between 1987 and 2006 describing inactivated seasonal influenza vaccine immunogenicity studies conducted in the United States, Canada, Europe, Israel, and Russia 10 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 . We included 129 independent study arms of which 119 reported data on response to A/H1N1, 109 on influenza B, and 108 on A/H3N2 vaccine strains (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Amongst the 14 studies included in this review, 8 reported seroprotection rates (Ruf et al, 2004;MacKenzie, 1977;Peters et al, 1988;Delafuente et al, 1998;Buxton et al, 2001;Brydak et al, 2003;Praditsuwan et al, 2005;Hui et al, 2006) and 6 seroconversion rates alone (McElhaney et al, 1993;Powers et al, 1995;Van Hoecke et al, 1996;Minutello et al, 1999;Mysliwska et al, 2004;Keylock et al, 2007). Seroprotection rates according to CPMP criteria (Table 1) were maintained ≥4 months after influenza immunization in all 8 for A/H3N2 com-ponent and in 5 of 7 studies for the A/H1N1 and B components.…”
Section: Is the Protective Hai Titre Decline Throughout The Influenzamentioning
confidence: 90%
“…In determining whether serological CPMP criteria were met at season's end, seroprotection rates of 70-100% were maintained not just at 4 months (Delafuente et al, 1998;Buxton et al, 2001) but also at 5 months (Peters et al, 1988;Brydak et al, 2003) and, even at >6 months (Ruf et al, 2004;MacKenzie, 1977;Praditsuwan et al, 2005;Hui et al, 2006) for the A/H3N2 and A/H1N1 vaccine components. In 2 of 6 studies reporting seroconversion alone, criteria were still met at 4 months (Van Hoecke et al, 1996;Mysliwska et al, 2004). Six studies had compared antibody persistence regarding the age with no significant difference between groups (3 compared elderly with young adults (MacKenzie, 1977;Brydak et al, 2003;McElhaney et al, 1993) and 3 compared aged individuals by advancing age (Peters et al, 1988;Praditsuwan et al, 2005;Van Hoecke et al, 1996)).…”
Section: Is the Protective Hai Titre Decline Throughout The Influenzamentioning
confidence: 99%
See 1 more Smart Citation